Solusi Persamaan Laplace pada Koordinat Bola - Ahmad Zaki; Syafruddin Side; Nurhaeda (Jurusan Matematika FMIPA UNM, 2019)
This study examines Laplace equations on spherical coordinates and applies variable separation methods in determining Laplace equation solutions Laplace equations are one type of partial differential equation that is widely used to model problems in the field of science. The general form of the Laplace equation in the third dimension in which u is a scalar function using the separation method of the variable is obtained by the third dimension Laplace equation on spherical coordinates. The result of this research get solution of Laplace equation on spherical coordinate in the form of separate variable by not using boundary value. The relationship of cartesian coordinates and spherical coordinates to the Laplace equation can be determined in the Laplace equation and obtain solutions using spherical coordinates.